Recovery of cell cycle delay following targeted gene repair by oligonucleotides - Ferrara, Luciana (2007)
We have previously shown that activation of the homologous recombinational repair pathway leads to a block of cell division in corrected cells, possibly through the activity of checkpoint proteins Chk1 and Chk2. In this study, we examine the long term impact of this stalling on the growth of cells that have enabled gene repair events. Using a mutated eGFP gene as an episomal reporter, we show that corrected (eGFP positive) cells contain only a few active replication templates two weeks after electroporation, yet do not display an apoptotic or senescent phenotype. By six weeks after electroporation, cells resume active replication with a cell cycle profile that is comparable to that of the non-corrected (eGFP negative) population. These results indicate that the initial stalling is transient and eGFP positive cells eventually resume a normal phenotypic growth pattern, allowing for passaging and expansion in vitro.